Islamic Sharia in The Regulations Regarding Adultery in The National Criminal Code - Fransiskus Saverius Nurdin (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The rapid progress of science (logical positivism) impacts technological progress. The onslaught of scientific progress has also impacted legal science, which requires law to be logical and free of values, including religious values. This article starts with the question of whether the regulation of the crime of adultery in the National Criminal Code is devoid of Islamic Sharia, like the old Criminal Code. This article discusses two brief points: first, how adultery is defined according to the legal reasoning of the national Criminal Code; second, how adultery is defined according to the logic of Islamic Sharia and its integration into the regulation of adultery in the national Criminal Code. This article results from library research with statutory and Islamic Sharia approaches. This article finally states first: in terms of legal reasoning, the national Criminal Code has regulated in detail the crime of adultery, namely Article 411 (adultery), Article 412 (cohabitation), and Article 413 (incest), second: Islamic legal reasoning recognizes two types of adultery, namely muḥṣan and ghair muḥṣan adultery and Article 411 is substantially inspired by the narration of Uqbah bin Amir al-Jahni Ra. The narration of the companion Jabir Ra essentially inspires article 412. Article 413 is substantially inspired by the letter QS al-Nisa 4:23. So, in the end, this article concludes that the regulation regarding the crime of adultery in the national Criminal Code is not free from religious values but rather is constitutively the result of the integration of Islamic Sharia.